2018
DOI: 10.1016/j.jmii.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic administration of voriconazole with two different doses for invasive fungal infection in children and adolescents with acute myeloid leukemia

Abstract: More dose escalation is required based on this study. As VRCZ concentration is considerably influenced by genetic polymorphisms and drug-drug interactions, VRCZ should be used under therapeutic drug monitoring to keep effective drug concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Total drug concentration of VRC in 932 plasma samples from 193 patients were determined by a HPLC-MS/MS method. The C max (1336 ± 676 ng/ml) in steady state of VRC reached therapeutic window (1,000-5,500 ng/ml) (Cabral-Galeano et al, 2015;Sano et al, 2018). However, there was still wide inter-individual variability in plasma concentration of VRC mostly associated with the diversity of metabolic types (CYP2C19) (Hamadeh et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Total drug concentration of VRC in 932 plasma samples from 193 patients were determined by a HPLC-MS/MS method. The C max (1336 ± 676 ng/ml) in steady state of VRC reached therapeutic window (1,000-5,500 ng/ml) (Cabral-Galeano et al, 2015;Sano et al, 2018). However, there was still wide inter-individual variability in plasma concentration of VRC mostly associated with the diversity of metabolic types (CYP2C19) (Hamadeh et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…They are also close to the loading dose of 7 mg/kg BID recommended by the Infectious Disease Society of America (IDSA) (Pappas et al, 2009), except for 12 mg/kg, which is the recommended dosage for 2-6-year-old NMs. Although the tolerance of higher dosage up to 10 mg/kg in children has been confirmed (Sano et al, 2016), further validation of this regimen's exposure and safety is needed before implementing it in clinical practice. In other subpopulations, dose adjustment is proposed based on several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we administered VRCZ as IFI prophylaxis for patients with AML. 15 However, the effectiveness of VRCZ for prophylaxis of IFI was inconsistent. This has prompted us to attempt dose adjustment of prophylactic VRCZ using blood concentration for patients with AML.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, we found AML, recurrent disease, and age over 9 years as risk factors for IFI. Hence, we administered VRCZ as IFI prophylaxis for patients with AML 15 . However, the effectiveness of VRCZ for prophylaxis of IFI was inconsistent.…”
Section: Discussionmentioning
confidence: 99%